Pengaruh Program Insentif Kasir Dalam Meningkatkan Jumlah Transaksi Layanan QRIS Ezeelink Pada Outlet Karnivor & Nanny’s Pavillon Cabang PIK 2 & SMB - Ananda Nur Fakhirah (CV Edujavare Publishing, 2024)
In the rapidly evolving era of digitalization, QRIS Ezeelink payment services are becoming increasingly vital as an integral part of retail businesses. However, Karnivor & Nannys Pavillon Outlet Branch PIK 2 & SMB faces a lack of adoption of this service, indicating challenges in digital payment technology acceptance among customers. This study aims to evaluate the impact of cashier incentive programs on increasing the number of QRIS Ezeelink transactions at the outlet. Using the audit humas method, surveys of cashiers and analysis of transaction data from the Ezeelink payment dashboard were conducted to understand the dynamics of service usage. The research findings reveal a noticeable absence of transactions since the installation of QRIS Ezeelink at the PIK 2 & SMB outlet, indicating low service adoption. Cashier incentive programs were implemented to stimulate transaction increases. Through in-depth analysis, it is hoped that the real influence of cashier incentive programs on the adoption of QRIS Ezeelink services at the outlet can be identified. This study holds significant relevance in the context of digital payment service development in the retail sector, with the hope of providing valuable insights for the related industry